Postawa Kościoła wobec przejawów cywilizacji śmierci u początków ludzkiego życia - Kluz, Marek (Studia Pastoralne, 2026)
Church – faithful to the mission commissioned by Christ – take successively the topics that appear throughout the history of mankind, which are the result of scientific development and progress of civilization, and increasing the possibility of interfering with the processes of life – from procreation, and the dying ending. Undoubtedly, the field of interference in human procreation is the one that because of the tremendous progress achieved and the personal good, especially endangered in its activities – requires special vigilance of the Church. Therefore, in this publication is presented clear moral teaching of the Church concerning the abuses in the field of procreation. For the fundamental fraud, which became the subject of moral reflection should include: contraception, morning after pill, sterilization and abortion, in vitro fertilization and cloning. It should be noted that all these issues related to human reproduction right contradict the Christian tradition for centuries, and above all the Church’s thought for contemporary view of marriage, family, sexuality and fertility. Break for inner unity, mutuality and the need for relationships between spouses, but also the relationships between parents and offspring. For this reason, must be evaluated negatively. These phenomena are in fact the opposite nature – sexuality without procreation on the one and procreation without sexuality on the other.